A CONTENT ANALYSIS OF ENGLISH TEXTBOOK â€œBAHASA INGGRIS; STOP BULLYING NOW 2017â€ ON THE BASIS OF CURRICULUM 2013 - Nurmahenis Nurmahenis; Syofia Delfi; Syarfi Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Textbook is a book that serves as a guideline for learners and teachers in supporting in teaching and learning process. In this study aims to analyze the English textbook based on BSNP. This research attempted to discover whether or not the English textbooks analyzed met the criteria of a good textbook adapted from BSNP instrument and whether it was relevant to the 2013 Curriculum and to find out how those criteria were fulfilled or not by those textbooks. This research design was content analysis with descriptive qualitative method, the subject of this research was English textbook entitled â€œBahasa Inggrisâ€ for second grade of Senior High School, the data source in this research were documents, the technique to collecting the data was content analysis technique. The result of the research showed that Bahasa inggris textbook had met the criteria of good textbook with the fulfillment 84.77 % The textbook was relevant to the 2013 Curriculum because most of the aspect in core competence and basic competence of 2013 Curriculum were reflect in the textbook. Teacher needs to seek out the compatibility of the textbook to use. This book met the most of the requirements and standart of a textbook in implementing 2013 Curriculum. By using this book in teaching and learning process, hopefully a good result is achieved. Through this research, evaluators can understand the result of evaluation by following standard BNSP which minister by education minister. Besides, evaluators can use this information and compare with standard evaluation based on experts to meet good criteria of English textbook.Keywords: textbook, 2013 Curriculum , BSNP instrument for textbook evaluation